Estimation of Some Antiviral Drugs Using Tpooo as Analytical Reagent - P. Venkata Reddy; B. Sudha Rani (E-Journal of Chemistry)
A simple and reproducible spectrophotometric method has been developed for the determination of two recent antiviral drugs namely Valacyclovir (drug A) and Famciclovir (drug B) in bulk and pharmaceutical dosage forms. The method is based on the extraction of the drugs into organic layer of the dye TPooo in presence of 0.1 N hydrochloric acid and the absorbances were measured at 490 nm. The method was optimized using eight parameters.